Avaliação do papel de SIRT1 na progressão do melanoma - Pereira, Danilo Micali [UNIFESP] (2017)
Melanoma is a skin cancer originated from melanocytes and is characterized by its increasing incidence and for being highly lethal. Its development has been demonstrated to be involved in both genetic and epigenetic alterations. Epigenetics, in turn, includes mechanisms such as DNA methylation, histone modifications and chromatin remodeling which are altered in cancer cells. It is known that reactive oxygen species (ROS) are capable of leading to such changes. High levels of ROS can cause DNA damage, which requires chromatin remodeling to be repaired. Sirtuin-1 (SIRT1) is a NAD+ -dependent histone deacetylase is part of damage repair mechanisms e is recruited to DNA damage sites where it can lead to transcriptional repression. SIRT1 is widely described as a ROS-responsive protein and is found overexpressed in different cancer cell lines. In the adopted melanoma progression mouse model, the cell lines 4C (premalignant melanocyte), 4C11- (non-metastatic melanoma) and 4C11+ (metastatic melanoma) were underwent five sequential cycles of adhesion blockage, what provides a stressing microenvironment that promotes increased levels of ROS. SIRT1 expression in these cell lines is increased in the intermediate cell lines 4C and 4C11- when compared to melan-a and significantly reduced in the cell line 4C11+. The role of SIRT1 in cancer is still not fully understood. This deacetylase has been pointed out as a tumor promoter in colon and breast cancer and also linked to better prognosis in diverse tumor types. In this work, SIRT1 expression was stably reduced by shRNA with the aim of assessing its role in melanocyte malignant transformation and melanoma progression. The reduced expression of SIRT1 in the cell lines melan-a and 4C did not have major effects, however, it led to reduced colony formation and collective cell migration in the cell line 4C11+. In parallel, the cell line melan-a with reduced SIRT1 expression was submitted to five sequential cycles of adhesion blockage followed by limiting dilution. SIRT1 silencing highly impacted cell viability, although it could not avoid malignant transformation. These data point out an oncogenic character to SIRT1 in the adopted cell model and encourage further investigation to better understand its role in melanoma.